Pengaruh Kepemimpinan Kepala Desa Dan Partisipasi Masyarakat Terhadap Pemanfaatan Dana Desa - Karningsih Karningsih (Universitas 17 Agustus 1945 Semarang, 2024)
Regulations in the history of Village regulation, starting with the establishment of regulations regarding Villages, namely the enactment of Law Number 6 of 2014 concerning Villages, have given new enthusiasm to the community who have sometimes been spectators in development in the region. The community is given the authority to recognize their rights of origin (recognition), determine local scale authority and make local decisions for the benefit of the village community (subsidiarity), diversity, togetherness, mutual cooperation, kinship, deliberation, democracy, independence, participation, equality, empowerment and sustainability. In its implementation, especially regarding, among other things, the position of customary law communities, democratization, diversity, community participation, as well as progress and equitable development, there are still shortcomings, giving rise to disparities between regions, poverty, and socio-cultural problems that can disrupt the integrity of the Unitary State of the Republic of Indonesia, becoming an issue that interesting. This research method is a quantitative method with an explanatory research type. The sampling technique is systematic rondom sampling using an ordinal method, to determine the influence of each variable using the product mom hypothesis test, showing that there is an influence of the village head's leadership and community participation on the utilization of village funds.